The Witch of Cologne - Learner, Tobsha (Australia Harper Collins Publishers, 2004)
Presents the story of Ruth bas Elazar Saul, a Jewish midwife who returns to her home, outside Cologne. Imbued with the radical ideas of Spinoza and with ancient Hebrew Kabbalism, her methods of dealing with illness lead to accusation of witchcraft and imprisonment. From the author of "Quiver", this is a love story of the 17th century.
Keywords: Germany--Cologne -- Jewish women -- Midwives